MARKET TESTING AND CONTRACTING-OUT OF GOVERNMENT CORPORATE SERVICE - Nick Sciulli; Victoria Wise (Universitas Trisakti, 2013)
The objective of this study is to identify specific issues considered to be major implementation obstacles by managers faced with the policy decision to shift services to the private sector. The shifting (contracting-out) of corporate services in a large government organisation is used as a case study to identify issues impacting on management decision-making in the contracting-out process. Matters such as the organisational approach to determination of service costs and changes to the stock of organisational knowledge are considered. Important findings include that an unusual and possibly unique integrated model for contracting-out was used; and, that managers adopted an avoidable-cost approach in contracting-out decisions.Keywords: Contracting-out; Government; Integrated model